Anticorrosive properties of nano silicate from paddy husk in salt medium - Norinsan Kamil Othman; Solhan Yahya; Denni Asra Awizar (Penerbit Universiti Kebangsaan Malaysia, 2016)
Anticorrosive properties of nano silicate from paddy husk in salt medium was investigated via weight loss method, Tafel polarization and impedance techniques. Prior to the corrosion test, the silica powder was obtained from burning the rice husk and extended with a chemical treatment process. The size of silica powder was characterized via zeta sizer and showed the amount of micro silica particle appear more than the nano size particle. Nano silica powder was produced from the refluxing process of micro silica to enhance the good properties of silica particle. The corrosion inhibition efficiency of nano silicate showed good inhibition with increased in inhibitor concentrations. Weight loss test exhibits high inhibition as more than 80% even, immersed in the corrosive medium until 14 days. The nano silicate inhibitor affected the anodic reaction as showed by Tafel plot analysis. Impedance results also correlated with other test as shown by the large size of Nyquist semicircle which represents as high resistance of charge transfer. The surface morphology of inhibited specimen showed a smooth surface after nano silicate inhibitor applied in the NaCl medium as observed through scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDX).